A clinicopathological approach to sulfur mustard-induced organ complications: a major review. (16th April 2013) - Ghasemi, Hassan; Owlia, Parviz; Jalali-Nadoushan, Mohammad Reza; Pourfarzam, Shahryar; Azimi, Ghasem; Yarmohammadi, Mohammad-Ebrahim; Shams, Jalaleddin; Fallahi, Faramarz; Moaiedmohseni, Sakine; Moin, Athar; Yaraee, Roya; Vaez-Mahdavi, Mohammad Reza; et al.
Abstract: Context : Sulfur mustard (SM), with an old manufacturing history still remains as potential threat due to easy production and extensive effects. Objectives : Increasing studies on SM indicates the interest of researchers to this subject. Almost all human body organs are at risk for complications of SM. This study offers organ-by-organ information on the effects of SM in animals and humans. Methods : The data sources were literature reviews since 1919 as well as our studies during the Iraq–Iran war. The search items were SM and its all other nomenclatures in relation to, in vivo, in vitro, humans, animals, eye, ocular, ophthalmic, lungs, pulmonary, skin, cutaneous, organs and systemic. Amongst more than 1890 SM-related articles, 257 more relevant clinicopathologic papers were selected for this review. Results : SM induces a vast range of damages in nearly all organs. Acute SM intoxication warrants immediate approach. Among chronic lesions, delayed keratitis and blindness, bronchiolitis obliterans and respiratory distress, skin pruritus, dryness and cancers are the most commonly observed clinical sequelae. Conclusion : Ocular involvements in a number of patients progress toward a severe, rapid onset form of keratitis. Progressive deterioration of respiratory tract leads to "mustard lung". Skin problems continue as chronic frustrating pruritus on old scars with susceptibility to skin cancers. Due to the multiple acute and chronic morbidities created by SM exposure, uses of multiple drugs by several routes of administrations are warranted.